THU0132 Prevalence and Predictive Value of Serum Autoantibodies in the General Population: Results of a Longitudinal Study on 2690 Subjects with a 13-Year Observation. (23rd January 2014) - Selmi, C.; Alborghetti, F.; Pfeiffer, S.; Colloredo, G.; Achenza, M. I.; Cavaciocchi, F.; Paleari, V.; Massarotti, M. S.; Brunetta, E.; Fabbriciani, G.; De Santis, M.; Meda, F.; et al.
Abstract : Background: The prevalence of serum autoantibodies in the general population is generally obtained from large datasets including blood donors or employees and are thus poorly representative. Similarly, it is challenging to determine the risk of developing an autoimmune disease in subjects found to be positive for serum autoantibodies in the absence of clinical suspicion. Objectives: To determine the prevalence and predictive value of ANA, ENA, and ACPA antibodies in the general population participating in a 13-year longitudinal study. Methods: The general population of a Northern Italian area was enrolled in 1998/1999 in a study to determine the prevalence of viral hepatitis infections. Resident subjects aged 18-75 were randomized 1:4 and 71% of subjects took part in the study (mean age 42, range 18-75, female/male 1.15). In 2011 serum samples (n=2690) were blindly tested for ANA, ENA, anti-CCP using commercially available indirect immunofluorescence and ELISA (Aesku.Diagnostics). For all subjects we sought for exemptions (i.e. the fiscal mechanism that allows subjects with a chronic condition to waive copayments for visits, medications, and blood tests) specific for autoimmune diseases (including connective tissue disease, CTD, and rheumatoid arthritis, RA) over the following 13 years. We should note that this approach does not account for 11% of the population which, for economic limits or advanced age, have a waiver overcoming the disease-specific exemptions. Administrative data were ultimately analyzed to determine the long-term predictive value of serum autoantibodies in terms of odd ratios (OR). Results: Serum ANA were detected in 18.1% (for titers ≥1:80) and 5.7% (for titers ≥1:160) of tested samples and the observed pattern was speckled in 71% of cases. The prevalence of specific anti-ENA autoantibodies ranged between 0.1% (Jo-1) and 1.9% (anti-nucleosome) while ACPA were positive in 4.7% of subjects (0.9% considering only medium-to-high titers). In all cases, prevalence rates were higher in female individuals but the predominance was lower than classically reported for CTD and RA. The OR for developing any autoimmune disease for ANA positive individuals over 13 years was 2.77 (95% confidence interval -CI- 1.73-4.44). The OR of developing a CTD for individuals with high-titer ANA was 12.20 (95% CI 2.41-61.59) while the OR of developing RA with positive ACPA was 10.86 (95% CI 1.96-59.98). Conclusions: We report that the prevalence of serum ANA, ENA, and ACPA may be higher than previously reported when a general unselected population is studied. Further, the serum positivity confers a significant risk of developing an autoimmune disease when subjects are observed for a sufficient period of time. Disclosure of Interest: None Declared